Exploring Students' Perceptions of Using Wordwall to English Learning Motivation at Junior High School - Ikafira Reviana; Karmila Machmud; Sri Agriyanti Mestari (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study explores junior high school students' perceptions and experiences of using Wordwall to support English learning motivation. It aims to understand how game-based media influences learning dynamics from the students' perspectives. Using a qualitative exploratory design, the study involved seven ninth-grade students and one English teacher at Junior High School as participants. Data were collected through in-depth interviews and analyzed using Reflexive Thematic Analysis. The findings reveal that Wordwall transforms previously passive classroom activities into interactive ones through visual stimulation and gaming mechanics. Based on the ARCS motivational framework, students' experiences are closely related to the dimensions of attention, relevance, confidence, and satisfaction. Despite facing technical infrastructure constraints, these findings suggest that the integration of digital media functions as an emotional bridge that reduces student anxiety and strengthens active engagement. This study concludes that the effectiveness of educational technology lies not only in its technical features but also in its ability to create a learning environment that supports students' affective domains.